Personal Hygiene Among School-Going Children in Morang District, Eastern Nepal - Koirala, Namu; Kafle, Shyam (Journal of Karnali Academy of Health Sciences, 2021)
Background: Personal hygiene includes cleanliness of the body and proper maintenance of personal appearance. This study aimed to identify the existing knowledge and practice of personal hygiene among lower secondary level school-going children in Morang, province one, in Eastern-Nepal. Methods: A quantitative, descriptive study was conducted in selected schools of Morang district, Eastern-Nepal comprising of 400 school children. Data was collected using a self-developed and validated structured questionnaire and observation checklist. Two schools from rural areas and two from urban areas were randomly selected and students from classes 6, 7 and 8 were also randomly selected for the study. Result: The majority of the students were in the age group 10-15 years (55% in urban areas and 50% in rural areas). Proper handwashing technique was reported by 59.5% of the students from the urban areas and 48.5% from rural areas. The majority of the students used toothpaste for brushing teeth in urban (79%) and rural areas (76%) respectively. For hand washing, 52% used soap in the urban areas whereas only 26% used soap in the rural area. Although knowledge and practice of personal hygiene were adequate, a significant gap was noted between them in the urban and rural areas (p<0.05). Conclusion: There was a significant gap between the knowledge and practice regarding the personal hygiene among the respondents both in the rural and in the urban areas. Adequate number of educational interventions has to be encompassed in the schools to increase the awareness among the students regarding this subject.